Post‐Synthetic Monovalent Central‐Metal Exchange, Specific I2 Sensing, and Polymerization of a Catalytic [3×3] Grid of [CuII5CuI4L6]⋅(I)2⋅13 H2O. Issue 20 (20th March 2013) - Han, Yi; Chilton, Nicholas F.; Li, Ming; Huang, Chao; Xu, Hong; Hou, Hongwei; Moubaraki, Boujemaa; Langley, Stuart K.; Batten, Stuart R.; Fan, Yaoting; Murray, Keith S.
Abstract From a predesigned grid, [CuII5CuI4L6]⋅(I)2⋅13 H2O (1), in which LH2 was a pyrazinyl‐triazolyl‐2, 6‐substituted pyridine, we successfully synthesized an extended 3D complex, 1∞[CuII5CuI8L6μ‐[CuI3(CN)6]2⋅2 CH3‐ CN] (2), that displayed unprecedented coexistence of all the five known coordination geometries of copper. Grid 1 displayed monovalent central metal exchange (CME) of CuI for AgI for the first time, as well as the formation of tri‐iodide in the crystalline state. These systems were investigated for their magnetic properties. Remarkably, grid 1 showed much higher catalytic activity than the Ag‐exchanged product for synthesis of a substituted triazole, 1‐benzyl‐4‐phenyl‐1H‐1, 2, 3‐triazole.